Intracranial aneurysms managed by parent artery reconstruction using Tubridge: Study protocol for a prospective, multicenter, post-market clinical trial. Issue 4 (August 2021) - Wu, Qiaowei; Li, Li; Shao, Qiuji; Xu, Tianming; Chang, Kaitao; Li, Tianxiao; He, Yingkun
Background: As a new endovascular reconstruction technique, flow diverter (FD) shows excellent efficacy and safety for treatment of intracranial aneurysms. In a previous multicenter, randomized, controlled, pre-market study, Tubridge FD showed remarkably higher complete occlusion rate compared with traditional stent-assisted coiling. However, a nonsignificant higher complication rate in the Tubridge group was noted. Considering the learning curve, the safety, and long-term outcomes of Tubridge FD should be verified in new prospective, real world, multicenter, post-market trials. Methods: This study is a prospective, multicenter, single-arm, post-market clinical trial that evaluates the safety and efficacy of Tubridge in the treatment of patients with intracranial aneurysms by reconstructing parent artery. We expect 200 participants who meet the inclusion and exclusion criteria to be included. Clinical information and angiographic results (Raymond–Roy grading scale, RRGS) will be recorded objectively. The primary endpoint will be the complete occlusion rate of the target aneurysm (RRGS 1) at 12-month follow-up. Secondary endpoints will include the adequate occlusion rate (RRGS 1 & 2) and the rate of major in-stent stenosis (>50%) at 12-month follow-up, technique success rate, changes of modified Rankin Scale before and after the procedure, the rate of aneurysm related disability, neurological mortality, and all-cause mortality within follow-up period. Discussion: This post-market, prospective trial may offer more information on the safety and long-term outcomes of Tubridge FD. When the study is complete, the results may provide us a new strategy for the treatment of intracranial aneurysms. Trial registration: WHO-Chinese Clinical Trial Registry: ChiCTR2000032282.